Preparation method of copper-tin-based Fe element doping proportion controllable catalyst for carbon dioxide reduction
Through the preparation method of doping Fe elements on copper-tin-based substrates, the problems of selectivity, conductivity and yield of existing electrocatalysts in the CO2 reduction process are solved, and the effects of process simplification, energy consumption reduction and catalytic performance improvement are achieved.
Patent Information
- Application Number
- CN202311125452.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-04
- Publication Date
- 2025-03-04
AI Technical Summary
The existing electrocatalysts have low selectivity, conductivity and yield in the CO2 reduction process, and the commonly used doping methods are cumbersome and have large energy consumption.
A preparation method with controllable proportion of Fe elements doped on copper-tin-based groups is adopted. By placing a solution containing Cu, Sn and Fe, and magnetic stirring is constant temperature in a 50°C water bath, then sodium borohydride solution is added, mechanical stirring and titration reaction is carried out, and Fe-doped copper-tin-based electrocatalyst is obtained by freeze-drying.
This method simplifies the preparation process, reduces energy consumption, improves the selectivity and conductivity of the catalyst, and promotes the improvement of electrochemical performance.
Smart Images

Figure CN119553303A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of chemical synthesis, and in particular to a method for preparing a catalyst doped with a controllable ratio of Fe element on a copper-tin base for carbon dioxide reduction, providing a preparation method with simple process and low cost. Background Art
[0002] Currently, the world is trapped in the fossil fuel economy. Due to the excessive consumption of these non-renewable fossil fuels and the excessive emission of CO2, energy and environmental problems are becoming increasingly serious. In order to alleviate the above problems, the development of a sustainable and reliable system to convert CO2 into valuable chemical fuels has attracted widespread research interest. Among all CO2 conversion methods, converting CO2 using electricity generated by wind or solar energy can achieve a sustainable zero-carbon cycle and store electrical energy in the form of chemical fuels. In a typical electrolyzer, CO2 at the cathode can be reduced to a variety of carbon-containing products. However, CO2 is an inert gas, and the electrochemical reduction of CO2 involves multiple proton-coupled electron transfer steps, which means that a larger overpotential is required in the process, and when aqueous solution is used as the electrolyte, it must compete with the hydrogen evolution reaction at the anode, resulting in harsh conditions and low efficiency for CO2. In addition, the adsorption of different intermediates in the reaction process and the diversity of products also lead to poor product selectivity. Therefore, reliable electrocatalysts are urgently needed to accelerate the slow eCO2RR and improve the catalytic performance.
[0003] In practical applications and catalytic processes, in order to further improve the adsorption of certain specific intermediates by the catalyst, the modification method of heteroatom doping is often used, and the adsorption effect of the doped atoms on the intermediates is used to improve the performance of the catalyst. The current common doping method is the solid phase method, which requires heat treatment such as high temperature and high pressure, has high energy consumption and a relatively cumbersome preparation process. Therefore, developing an electrocatalyst with low cost, simple preparation process, high selectivity and conductivity is an important research goal in the field of electrocatalytic reduction of CO2. Summary of the invention
[0004] In view of the problems of low selectivity, conductivity and yield of current electrocatalytic reduction of CO2 catalysts, the present invention proposes a preparation method for doping a copper-tin base with a controllable proportion of Fe element, which can effectively improve the problems of complicated process and high energy consumption in the commonly used doping process.
[0005] To achieve the above object, the present invention provides the following technical steps:
[0006] (1) Prepare a solution containing Cu, Sn and Fe and keep it in a 50°C water bath with magnetic stirring for 25 min.
[0007] (2) Prepare sodium borohydride solution and stir mechanically at room temperature.
[0008] (3) Add the solution in (1) dropwise into the solution in (2) to obtain a black suspension.
[0009] (4) The black suspension in (3) is repeatedly centrifuged and ultrasonically cleaned.
[0010] (5) The suspension after washing in (4) is freeze-dried to obtain a copper-tin matrix doped with Fe / Co / Ni.
[0011] In the preferred step (1), 3 mol / L HCl solution is first added to 20 mL of deionized water to prepare a dilute hydrochloric acid solution, and then CuCl2·6H2O, SnCl2·6H2O and FeCl3·6H2O are added to the dilute hydrochloric acid solution to prepare a solution in which Cu, Sn and Fe elements coexist.
[0012] Preferably, in step (2), sodium borohydride is dissolved in deionized water, and the concentration of the sodium borohydride solution is 0.3 mol / L.
[0013] Preferably, in step (3), a rubber-tipped dropper is used for dripping, the rate is controlled at 2 drops / s, and magnetic stirring is performed at room temperature during dripping.
[0014] In the preferred step (3), after the titration is completed, the rotation speed needs to be maintained for 10 minutes to allow for sufficient reaction, and then the mixture is allowed to stand for 10 minutes.
[0015] Preferably, in step (4), the centrifugal speed is 8800 r / min, the duration is 5 min, and the reagent used for ultrasonic cleaning is deionized water.
[0016] Preferably, in step (4), centrifugation and ultrasonic cleaning are repeated alternately for a total of 6 times.
[0017] Preferably, in step (5), the freeze-drying time is 5-10 hours.
[0018] The present invention has the following beneficial effects:
[0019] 1. The preparation method adopts a one-pot method, that is, the required sample precursor hydrate is dissolved in a hydrochloric acid solution and reduced to a solid sample with a strongly reducing sodium borohydride solution. By changing the type of precursor hydrate, different elements can be combined, which has a certain degree of versatility. In addition, by adjusting the amount of precursor hydrate, the element ratio of the prepared sample can also be adjusted, which is convenient for further discussion of the catalytic performance of different elements and ratio combinations for electrochemical reduction of CO2
[0020] 2. The sample size is composed of irregular small particles ranging from 20 to 100 nm, with many holes in between. The unique microstructure can expose more active sites on the one hand, and accelerate electron transfer and improve conductivity on the other hand, thereby promoting the improvement of electrochemical performance.
[0021] 3. Freeze drying is used for sample post-processing. Compared with traditional drying, it can effectively prevent metal element oxidation in a low temperature and vacuum environment. Secondly, the sample obtained by direct solvent vaporization is fine powder particles, which can be better dissolved in the slurry, simplifying the subsequent electrode preparation process.
[0022] 4. The preparation method proposed in the present invention has simple equipment, readily available materials, convenient operation, low condition requirements, low energy consumption, high repeatability, and is easy for mass production. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 This is a cold-field scanning electron microscopy image of the Fe-doped copper-tin-based electrocatalyst prepared in Example 1.
[0024] Figure 2 This is the X-ray diffraction pattern of the Fe-doped copper-tin-based electrocatalyst prepared in Example 1.
[0025] Figure 3 This is the linear sweep voltammetry curve of the Fe-doped copper-tin-based electrocatalyst prepared in Example 1.
[0026] Figure 4 This is a cold-field scanning electron microscopy image of the Co-doped copper-tin-based electrocatalyst prepared in Example 2.
[0027] Figure 5 This is the X-ray diffraction pattern of the Co-doped copper-tin-based electrocatalyst prepared in Example 2.
[0028] Figure 6 This is the linear sweep voltammetry curve of the Co-doped copper-tin-based electrocatalyst prepared in Example 2.
[0029] Figure 7 This is a cold-field scanning electron microscopy image of the Ni-doped copper-tin-based electrocatalyst prepared in Example 3.
[0030] Figure 8 This is the X-ray diffraction pattern of the Ni-doped copper-tin-based electrocatalyst prepared in Example 3.
[0031] Fig. 9 This is the linear sweep voltammetry curve of the Ni-doped copper-tin-based electrocatalyst prepared in Example 3.
[0032] Fig.10 This is a cold-field scanning electron microscopy image of the Co-doped copper-tin-based (Cu:Sn:Co=4:1:0.1) electrocatalyst prepared in Example 4.
[0033] Fig.11 This is a cold-field scanning electron microscopy image of the Co-doped copper-tin-based (Cu:Sn:Co=4:1:0.3) electrocatalyst prepared in Example 5.
[0034] Fig.12 This is a cold-field scanning electron microscopy image of the copper-tin-based (Cu:Sn=4:1) electrocatalyst prepared in Example 6.
[0035] Fig.13 This is the linear sweep voltammetry curve of the copper-tin-based (Cu:Sn=4:1) electrocatalyst prepared in Example 6.
[0036] Fig.14 This is the XRD pattern of the copper-tin based (Cu:Sn=1:4) electrocatalyst prepared in Example 7.
[0037] Fig.15 This is the linear sweep voltammetry curve of the copper-tin based (Cu:Sn=1:4) electrocatalyst prepared in Example 7. DETAILED DESCRIPTION
[0038] The present invention is described in detail below in conjunction with specific embodiments and corresponding drawings. The technology of the present invention is not limited to the specific embodiments listed below, but also includes any combination of specific embodiments. Any modifications and improvements made without departing from the concept of the present invention belong to the protection scope of the present invention.
[0039] Example 1
[0040] (1) Prepare solutions of Cu, Sn and Fe and place them in a 50°C water bath with constant magnetic stirring for 25 min.
[0041] (2) Prepare sodium borohydride solution and stir mechanically at room temperature.
[0042] (3) Add the solution in (1) dropwise into the solution in (2) to obtain a black suspension.
[0043] (4) The black suspension in (3) is repeatedly centrifuged and ultrasonically cleaned.
[0044] (5) The suspension after washing in (4) is freeze-dried to obtain a Fe-doped copper-tin matrix.
[0045] In the preferred step (1), 3 mol / L HCl solution is first added to 20 mL of deionized water to prepare a dilute hydrochloric acid solution, and then CuCl2·6H2O, SnCl2·6H2O and FeCl3·6H2O are added to the dilute hydrochloric acid solution at a molar ratio of 4:1:0.2 to prepare a solution in which Cu, Sn and Fe coexist.
[0046] Preferably, in step (2), sodium borohydride is dissolved in deionized water, and the concentration of the sodium borohydride solution is 0.3 mol / L.
[0047] Preferably, in step (3), a rubber-tipped dropper is used for dripping, the rate is controlled at 2 drops / s, and magnetic stirring is performed at room temperature during dripping.
[0048] In the preferred step (3), after the titration is completed, the rotation speed needs to be maintained for 10 minutes to allow for sufficient reaction, and then the mixture is allowed to stand for 10 minutes.
[0049] Preferably, in step (4), the centrifugal speed is 8800 r / min, the duration is 5 min, and the reagent used for ultrasonic cleaning is deionized water.
[0050] Preferably, in step (4), centrifugation and ultrasonic cleaning are performed alternately for a total of 6 times.
[0051] Preferably, in step (5), the freeze-drying time is 5-10 hours.
[0052] Figure 1 This is a cold field scanning electron microscope image of the Fe-doped copper-tin-based electrocatalyst prepared in the present invention, indicating that the sample obtained after doping the copper-tin base with iron is composed of irregular small particles with a size of 20-100 nm.
[0053] Figure 2 The X-ray diffraction pattern of the Fe-doped copper-tin-based electrocatalyst prepared in the present invention corresponds to JCPDS standard card No. 80-1916, indicating that the main component of the material is composed of CuO, and no other impurity peaks exist, and the sample purity is high. Further combined with the chromatogram, it can be observed that a large amount of Sn and a small amount of Fe elements exist, and the Fe element is successfully doped on the copper-tin base.
[0054] Figure 3 The linear sweep voltammetry curve of the Fe-doped copper-tin-based electrocatalyst prepared in the present invention, the solid line and the dotted line are the comparison of the catalyst performance under carbon dioxide and argon, respectively, and the carbon dioxide reduction performance is significant, indicating that Fe doping may improve the adsorption of certain specific intermediates to enhance the overall electrochemical performance, and improve the conductivity to a certain extent.
[0055] Example 2
[0056] The difference between Example 2 and Example 1 is that the precursor hydrates used in Example 2 are CuCl2·6H2O, SnCl2·6H2O and Co(NO3)2·6H2O.
[0057] Figure 4 This is a cold field scanning electron microscope image of the Co-doped copper-tin-based electrocatalyst prepared in the present invention, indicating that the sample obtained after doping the copper-tin base with iron is composed of irregular small particles with a size of 20-100 nm.
[0058] Figure 5The X-ray diffraction pattern of the Co-doped copper-tin-based electrocatalyst prepared in the present invention corresponds to JCPDS standard card No. 80-1916, indicating that the main component of the material is composed of CuO, and no other impurity peaks exist, and the sample purity is high. Further combined with the chromatogram, it can be observed that a large amount of Sn and a small amount of Co elements exist, and the Co element is successfully doped on the copper-tin base.
[0059] Figure 6 The linear sweep voltammetric curve of the Co-doped copper-tin-based electrocatalyst prepared in the present invention is shown in Figure 1. The solid line and the dotted line are the comparison of the catalyst performance under carbon dioxide and argon respectively. The carbon dioxide reduction performance is significant, indicating that the doping of Co may improve the adsorption of certain specific intermediates to improve the overall electrochemical performance and improve the conductivity to a certain extent. Compared with other embodiments, this embodiment shows the best electrochemical performance, indicating the contribution of the present invention to the field of electrocatalytic reduction of CO2 by adjusting the product ratio.
[0060] Example 3
[0061] The difference between Example 3 and Example 1 is that the precursor hydrates used in Example 3 are CuCl2·6H2O, SnCl2·6H2O and Ni(NO3)2·6H2O.
[0062] Figure 7 This is a cold field scanning electron microscope image of the Ni-doped copper-tin-based electrocatalyst prepared in the present invention, indicating that the sample obtained after iron is doped on the copper-tin base is composed of irregular small particles with a size of 20-100 nm.
[0063] Figure 8 The X-ray diffraction pattern of the Ni-doped copper-tin-based electrocatalyst prepared in the present invention corresponds to JCPDS standard card No. 80-1916, indicating that the main component of the material is composed of CuO, and no other impurity peaks exist, and the sample purity is high. Further combined with the chromatogram, it can be observed that a large amount of Sn and a small amount of Ni elements exist, and the Ni element is successfully doped on the copper-tin base.
[0064] Fig. 9 The linear sweep voltammetry curve of the Ni-doped copper-tin-based electrocatalyst prepared in the present invention, the solid line and the dotted line are the comparison of the catalyst performance under carbon dioxide and argon, respectively, and the carbon dioxide reduction performance is significant, indicating that Ni doping may improve the adsorption of certain specific intermediates to enhance the overall electrochemical performance, and improve the conductivity to a certain extent.
[0065] Example 4
[0066] The difference between Example 4 and Example 2 is that the molar ratio of the precursor hydrate used in Example 4 is CuCl2·6H2O: SnCl2·6H2O: Co(NO3)2·6H2O=4:1:0.1.
[0067] Fig.10 This is a cold field scanning electron microscope image of the Co-doped copper-tin-based (Cu:Sn:Co=4:1:0.1) electrocatalyst prepared in the present invention, indicating that the sample obtained after doping Co on the copper-tin base is composed of irregular small particles with a size of 20-100nm.
[0068] Example 5
[0069] The difference between Example 5 and Example 2 is that the molar ratio of the precursor hydrate used in Example 5 is CuCl2·6H2O: SnCl2·6H2O: Co(NO3)2·6H2O=4:1:0.3.
[0070] Fig.11 This is a cold field scanning electron microscope image of the Co-doped copper-tin-based (Cu:Sn:Co=4:1:0.3) electrocatalyst prepared in the present invention, indicating that the sample obtained after doping Co on the copper-tin base is composed of irregular small particles with a size of 20-100nm.
[0071] Example 6
[0072] The difference between Example 6 and Example 1 is that the precursor hydrate and the molar ratio used in Example 6 are CuCl2·6H2O:SnCl2·6H2O=4:1.
[0073] Fig.12 This is a cold field scanning electron microscope image of the copper-tin-based (Cu:Sn=4:1) electrocatalyst prepared in the present invention, which shows that the copper-tin-based sample is composed of irregular small particles with a size of 20-100 nm.
[0074] Fig.13 This is the linear sweep voltammogram of the copper-tin-based (Cu:Sn=4:1) electrocatalyst prepared in the present invention. The solid line and the dotted line are the comparison of the catalyst performance under carbon dioxide and argon, respectively. The carbon dioxide reduction performance is better, further indicating the possibility of the invention for preparing a rich CO2 reduction electrocatalyst composition.
[0075] Example 7
[0076] The difference between Example 7 and Example 1 is that the precursor hydrate and the molar ratio used in Example 7 are CuCl2·6H2O:SnCl2·6H2O=1:4.
[0077] Fig.14This is a cold field scanning electron microscope image of the copper-tin-based (Cu:Sn=1:4) electrocatalyst prepared in the present invention, which shows that the copper-tin-based sample is composed of irregular small particles with a size of 20-100 nm.
[0078] Fig.15 This is the linear sweep voltammogram of the copper-tin-based (Cu:Sn=1:4) electrocatalyst prepared in the present invention. The solid line and the dotted line are the comparison of the catalyst performance under carbon dioxide and argon, respectively. The carbon dioxide reduction performance is better, further indicating the possibility of the invention for preparing a rich CO2 reduction electrocatalyst composition.
[0079] The above is a preferred example of a method for preparing a copper-tin-based catalyst with a controllable Fe element ratio for carbon dioxide reduction disclosed and proposed by the present invention. For those skilled in the art, by referring to the contents of this article and appropriately changing the conditions and routes without departing from the principles of the present invention to achieve the final preparation technology, it should be regarded as the content and scope of the present invention.
Claims
1. A method for producing a copper-tin-based catalyst doped with a controllable Fe ratio for carbon dioxide reduction, characterized in that: The mixed solution is reduced by a reducing agent and then freeze-dried to obtain a metal-doped powder, which is composed of irregular small particles with a size of 20-100nm and a controllable element ratio.
2. The method for preparing a copper-tin-based catalyst doped with a controllable Fe ratio for carbon dioxide reduction as claimed in claim 1, characterized in that: The steps include: (1) Prepare a solution containing Cu, Sn and Fe and keep it in a 50°C water bath with magnetic stirring for 25 min. (2) Prepare sodium borohydride solution and stir mechanically at room temperature. (3) Add the solution in (1) dropwise into the solution in (2) to obtain a black suspension. (4) The black suspension in (3) is repeatedly centrifuged and ultrasonically cleaned. (5) The suspension after washing in (4) is freeze-dried to obtain a copper-tin matrix doped with Fe / Co / Ni.
3. The method according to claim 2, characterized in that In step 1), 3 mol / L HCl solution is first added to 20 mL of deionized water to prepare a dilute hydrochloric acid solution, and then CuCl2·6H2O, SnCl2·6H2O and FeCl3·6H2O are added to the dilute hydrochloric acid solution to prepare a solution in which Cu, Sn and Fe elements coexist.
4. The method according to claim 2, characterized in that In step 2), sodium borohydride is dissolved in deionized water, and the concentration of the sodium borohydride solution is 0.3 mol / L.
5. The method according to claim 2, characterized in that In step 3), a rubber-tipped dropper is used for dripping, and the rate is controlled at 2 drops / s, and magnetic stirring is performed at room temperature during dripping.
6. The method according to claim 2, characterized in that In step 3), after the titration is completed, the rotation speed needs to be maintained for 10 minutes to allow for sufficient reaction, and then allowed to stand for 10 minutes.
7. The method according to claim 2, characterized in that In step 4), the centrifugal speed is 8800 r / min, the duration is 5 min, and the reagent used for ultrasonic cleaning is deionized water.
8. The method according to claim 2, characterized in that In step 4), centrifugation and ultrasonic cleaning are repeated alternately for a total of 6 times.
9. The method according to claim 2, characterized in that In step 5), the freeze-drying time is 5-10 hours.